A long-term survival case of adult undifferentiated embryonal sarcoma of liver - Noguchi, Keita; Yokoo, Hideki; Nakanishi, Kazuaki; Kakisaka, Tatsuhiko; Tsuruga, Yosuke; Kamachi, Hirofumi; Matsushita, Michiaki; Kamiyama, Toshiya (World journal of surgical oncology, 2012)
Undifferentiated embryonal sarcoma of the liver (USEL) is a rare malignant hepatic tumor with a poor prognosis that is usually observed in children (aged 6 to 10 years) and rarely seen in adults. We present a case of USEL in a 27-year-old woman with no previous history of the disease. Laboratory tests performed on admission showed that the patient had mildly elevated levels of aspartate aminotransferase, alanine transaminase, alkaline phosphatase, lactate dehydrogenase, and γ-glutamyl transpeptidase. The levels of viral hepatitis and tumor serum markers were all within normal limits. Computed tomography showed a large mass involving the right lobe and the medial segment of the liver. Right trisectionectomy was performed. Microscopically, the tumor was composed of pleomorphic and polynuclear dyskaryotic cells in a myxoid stroma with focal eosinophilic globules and no clear differentiation to muscle. Histological diagnosis showed undifferentiated embryonal sarcoma. Adjuvant therapy with cisplatin, vincristine, doxorubicin, cyclophosphamide, and actinomycin D was initiated. We administered a high dose of etoposide to extract the patient's peripheral blood stem cells and performed radiation therapy and peripheral blood stem cell transplantation. At 5-year follow-up, the patient was alive without any evidence of recurrence. Here, we describe the clinical and histopathological features of USEL as well as the therapeutic options for USEL in adults with this disease.